NEEDS ANALYSIS OF HOTS INTEGRATED PROBLEM BASED LEARNING AND SOCIAL INCLUSSION INTERNET BASED LEARNING MODELS OF THINGS - Mangaratua Marianus Simanjorang; Bornok sinaga; Mardhatillah Mardhatillah (SENSEI RESEARCH CENTER, 2022)
The purpose of this research is to evaluate the development requirements for creating HOTS-based thematic elementary school teaching modules that are digitally connected. In North Sumatra Province, the study was carried out utilizing a survey method at 9 Elementary Schools. 18 teachers of thematic learning in the classroom served as the research participants. The subjects of the study were principals' and teachers' reactions to the emergence of problem-based learning (PBL) integrated classrooms and social inclusion, instructors' propensity to use theme models in the classroom, students' thinking, and students' character. Interviews, questionnaires, observations, and tests were used to obtain the data. Data were descriptively examined. The analysis' findings demonstrate that school administrators have not offered advice on creating thematic models, therefore they are supportive of development initiatives